An intensifying and elite city: New geographies of social class and inequality in contemporary London. Issue 1 (2nd January 2017) - Cunningham, Niall; Savage, Mike
Abstract : This paper contributes to the debate on London's social class structure at the start of the 21st century. That debate has focused on the use of census metrics to argue the case for whether or not the capital has become more or less middle class in composition between 2001 and 2011. We contend that the definition of the middle class has become confused in the course of this debate and is of less critical importance for an understanding of the city's contemporary class structure than is a focus on London's elite. We make use of data from the BBC's Great British Class Survey (GBCS) to shed light on the social, cultural and economic resources of this group, in addition to their spatial location. We then return to the census data for 2001 and 2011 and posit that belying the image of stability in London's class structure these data suggest clear and localised patterns of intensification in class geographies across the capital, an intensification characterised by a growing cleavage between Inner and Outer London.